Dissemination of a theory-based online bone health program: Two intervention approaches. (June 2015) - Nahm, Eun-Shim; Resnick, Barbara; Bellantoni, Michele; Zhu, Shijun; Brown, Clayton; Brennan, Patricia F; Charters, Kathleen; Brown, Jeanine; Rietschel, Matthew; Pinna, Joanne; An, Minjeong; Park, Bu Kyung; et al.
With the increasing nationwide emphasis on eHealth, there has been a rapid growth in the use of the Internet to deliver health promotion interventions. Although there has been a great deal of research in this field, little information is available regarding the methodologies to develop and implement effective online interventions. This article describes two social cognitive theory–based online health behavior interventions used in a large-scale dissemination study (N = 866), their implementation processes, and the lessons learned during the implementation processes. The two interventions were a short-term (8-week) intensive online Bone Power program and a longer term (12-month) Bone Power Plus program, including the Bone Power program followed by a 10-month online booster intervention (biweekly eHealth newsletters). This study used a small-group approach (32 intervention groups), and to effectively manage those groups, an eLearning management program was used as an upper layer of the Web intervention. Both interventions were implemented successfully with high retention rates (80.7% at 18 months). The theory-based approaches and the online infrastructure used in this study showed a promising potential as an effective platform for online behavior studies. Further replication studies with different samples and settings are needed to validate the utility of this intervention structure.